Implementasi Manajemen Peserta Didik Berbasis ICT di SMP MBS Zam Zam Cilongok - Wardani Vadila; Yosi Intan Pandini Gunawan (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research aims to explore the implementation of ICT-based learner management in education. In modern times like today, the role of ICT in the world of education is very important. schools are very important in producing young people who have good personalities and competencies that can compete globally. In addition, another role of schools is to produce graduates who are ready to carry out the development process in society. This research uses a qualitative approach. The subjects in this study were the principal of Zam Zam MBS Junior High School in Cilongok and the Head of PSB of Zam Zam MBS Junior High School. Data collection techniques used in this research are interviews, observation, and documentation. Data analysis techniques in this study are data reduction, data presentation, and data verification. The results of data analysis show that the implementation of new student enrollment at SMP MBS Zam Zam Cilongok has been successfully implemented properly through 4 management steps namely planning, organizing, implementing, and monitoring or evaluating. It can be concluded that with good student management, it will produce maximum processes and results